Nutritional Security in Drylands: Fast-Track Intra-Population Genetic Improvement for Grain Iron and Zinc Densities in Pearl Millet - Govindaraj, Mahalingam; Rai, Kedar Nath; Kanatti, Anand; Rao, Aluri Sambasiva; Shivade, Harshad (Frontiers in Nutrition, 2019)
Considering the pervasive malnutrition caused by micronutrients, particularly of that arising from the deficiencies of iron (Fe) and zinc (Zn), the primary focus of research in pearl millet is on biofortifying the crop with these two minerals. Pearl millet is a highly cross-pollinated crop wherein open-pollinated varieties (OPVs) and hybrids are the only two distinct cultivar types. In view of the severe setback of Fe and Zn deficiencies in Asia and Africa where this crop is widely consumed, crop biofortification will hold a key role in attenuate this crisis. The present study included three OPVs to assess the magnitude of variability and test the effectiveness of fast-track selection and improvement in an intra-population for Fe and Zn densities. Large variability among the S1 progenies was observed in all three OPVs, where the variability for Fe is quadrupled (31-143 mg kg-1) and that for Zn is doubled (35-82 mg kg-1). Progeny selection was effective for Fe density in all three OPVs, with up to 21% selection response for Fe density, and up to 10% selection response in two OPVs for Zn density, as an associated trait. Selection for Fe density had no adverse effect on grain yield and other agronomic traits. These results suggest that effective selection for Fe density in OPVs and composites can be made for these micronutrients and selection for Fe density is highly associated with the improvement of Zn density as well. These genetic changes can be achieved without compromising on grain yield and agronomic traits. This indicate that the increased frequency of favorable alleles for Fe and Zn densities while maintaining the genetic potential of these agronomic traits. Such improved versions could serve as essentially derived varieties for immediate cultivation or later may serve as potential sources for the development of better inbreds. This fast-track approach is the result of direct selection favoring additive genetic effects because there is no chance for masking action and it circumvents two to three cycles of selection gains. Therefore, fast-track breeding is essential to produce biofortified breeding pipelines to address food-cum-nutritional security.